Acupuncture at heterotopic acupoints facilitates distal colonic motility via activating M3 receptors and somatic afferent C‐fibers in normal, constipated, or diarrhoeic rats. Issue 12 (13th October 2015) - Gao, X.; Qin, Q.; Yu, X.; Liu, K.; Li, L.; Qiao, H.; Zhu, B.
Abstract: Background: Previous studies have demonstrated the efficacy of somatic stimulation for patients with gastrointestinal motility disorders. However, little effort has been made to investigate the effects of acupuncture on colonic motility, particularly in pathological conditions. The precise mechanism employed in the regulation of acupuncture on colonic motility still remains unclear. Methods: We assessed the effect of acupuncture at heterotopic acupoints on distal colonic motility using a warm‐water‐filled manometric balloon inserted 5–6 cm into the rectum of anesthetized normal rats or rats with diarrhea or constipation. Choline chloride, 4‐DAMP, cobra venom and capsaicin were separately applied to investigate the role of M3 receptors in the regulation of distal colonic motility by acupuncture at heterotopic acupoints, and whether A δ ‐ and/or C‐fibers are required for triggering distal colonic motility by acupuncture. Key Results: Acupuncture at heterotopic acupoints increased distal colonic motility not only in normal rats but also in rats with constipation or diarrhea. M3 receptors play an important role in the facilitation of distal colonic motility triggered by acupuncture at heterotopic acupoints. Afferent nerve A δ ‐ and C‐fibers mediate the transduction of the acupuncture signal and C‐fibers are essential for enhancing the effect of acupuncture at the heterotopic acupoint on distal colonic motility. Conclusions & Inferences: Our results reveal that acupuncture at heterotopic acupoints increases distal colonic motility regardless of normal or pathological conditions via predominately activating C‐fibers of somatic afferent nerve and M3 receptors. Abstract : Little effort has previously been made to investigate the effects of acupuncture on distal colonic motility, particularly in pathological conditions, and the precise mechanism employed in the regulation of acupuncture on colonic motility. In this study, our results reveal that acupuncture at heterotopic acupoints increases distal colonic motility not only in normal rats but also in rats with constipation or diarrhea via predominately activating C‐fibers of somatic afferent nerve and M3 receptors.